KINERJA PEMASARAN BERBASIS GENDER DIVERSITY - Ali Ali (JURNAL STIE SEMARANG, 2019)
Marketing performance has a very important role in UKM Furniture in Jepara Regency. The purpose of this study is to analyze marketing performance based on gender diversity. The implication for managerial and policy as a basis for solving marketing performance problems is based on gender diversity. Methodology: product innovation, marketing innovation, competitive advantage and network access will play an important role to measure marketing performance based on gender diversity. Based on empirical studies gender diversity has an important role in company policy, especially related to marketing performance. Women's gender has an influence on marketing performance of 80,247 compared to men's gender only has an effect of 58,753. Limitations of the study: only examined 5 variables influencing factors: product innovation, marketing innovation, competitive advantage, network access and marketing performance. Practical implications: product innovation, marketing innovation, competitive advantage and network access will affect marketing performance based on gender diversity.